Influence Of Brand Equity, Product Quality And Warranty On Consumer Purchasing Decisions (Study On Tupperware Products In Bengkulu City) - Ardiansyah, Yogi; Abdillah, Willy; Hayu, Rina Suthia (UNIB Press, 2024)
This study aims to analyze the effect of brand equity, product quality and warranty on consumer decisions to buy products. This type of research was used a quantitative descriptive approach with a survey method. In this study, the authors collected information data and basic information using a questionnaire distributed to respondents of Tupperware Bengkulu members. The data to be used in this study are primary data obtained directly from respondents of Tupperware Bengkulu members totaling 230 people. The data analysis method used descriptive analysis and partial least square analysis. The results showed that: (1) Brand equity has a positive and significant effect on consumer purchasing decisions on Tupperware products in Bengkulu City; (2) Product quality has a positive and significant effect on consumer purchasing decisions on Tupperware products in Bengkulu City; and (3) Warranty/guarantee has a positive and significant effect on consumer purchasing decisions on Tupperware products in Bengkulu City